Hubungan Antara Motivasi Kerja Dan Gaya Kepemimpinan Guru Dengan Pengelolaan Kelas - Fransiskus Jonet Prihandoko (Faktor Jurnal Ilmiah Kependidikan, 2018)
AbstractThe objective of this correlational research was to obtain the information concerning the correlation between work motivation and teachers’ leadership style to classroom management in Sekolah Dasar Pembangunan Jaya Bintaro, Tangerang. The population that is used for the respondent was 40 teachers and the research was held by using survey technique. There were 15 samples that was taken by using simple random sampling in this research. The analyzing  used  multiple regression and questioner sheet that was used  for collecting data. The research findings were (1) there was a positive significant correlation between work motivation with classroom management in Sekolah Dasar Pembangunan Jaya Bintaro because ? was less the significant level, namely  0.0000 < 0.05, and also the coefficient correlation was shown by ?1 = 0,341 with t score 2,062, Sig 0,046 means that if the teachers have good work motivation so that they can manage the class in a good condition  (2) there is a positive significant correlation between teachers’ leadership style with classroom management in Sekolah Dasar Pembangunan Jaya Bintaro because ? is less than the significance level, namely 0.000 < 0.05, and also the coefficient correlation is shown by ?2 = 0,368 with t score 2,104, Sig 0,042 means that if the teachers can use an appropriate leadership style to manage their class so that they can manage the class successfully (3) there is a positive significant correlation between both work motivation and teachers’ leadership style with classroom management in Sekolah Dasar Pembangunan Jaya Bintaro because ? is less than the significance level, namely 0.000 < 0.05, and also the coefficient correlation is shown by P-value = 0,002 means that if the teachers have good work motivation and use an appropriate leadership style so that they can manage their class in a good condition.The conclusion of this research were the variable of work motivation and teachers’ leadership style have the positive and significant  correlation with classroom management